Wound prevention education in diabetes melitus feet (Talenta Publisher, 2019)
Diabetes Mellitus is a chronic metabolic disease characterized by high blood sugar levels. Recorded as many as 382 million people in the world with the age of 40 - 59 years suffer from DM and are expected to continue to increase every year. At present diabetes in Indonesia is ranked seventh in the world. The main factors causing the increasing number of people with DM are lifestyle changes that include changes in diet, stress levels and sedentary lifestyle. In general, 90-95% of people with DM are type 2 DM, which generally occurs in people who are overweight (obese). In patients with type 2 DM increased blood sugar levels due to insulin resistance. Educating on prevention of diabetes foot injury to cadres by educating how to take care of your feet and diabetes exercises. The targets of this program are cadres and people with diabetes who are in the family and community. Through this education it is expected to avoid complications of diabetic foot injuries so that the quality of life becomes better.